A Detailed Spatial Expression Analysis of Wing Phenotypes Reveals Novel Patterns of Odorant Binding Proteins in the Soybean Aphid, Aphis glycines - Wang, Ling; Yin, Hang; Zhu, Zhiguo; Yang, Shuai; Fan, Jia (Frontiers in Physiology, 2021)
The wide range of insect niches has led to a rapid expansion of chemosensory gene families as well as their relatively independent evolution and a high variation. Previous studies have revealed some functions for odorant-binding proteins (OBPs) in processes beyond olfaction, such as gustation and reproduction. In this study, a comparative transcriptomic analysis strategy was applied for the soybean aphid, Aphis glycines, focusing on various functional tissues and organs of winged aphids, including the antenna, head, leg, wing, thorax, cauda, and cornicle. Detailed spatial OBP expression patterns in winged and wingless parthenogenetic aphids were detected by RT-qPCR. Twelve OBPs were identified, and three new OBPs in A. glycines are first reported. All OBPs showed comparatively higher expression in sensory organs and tissues, such as the antenna, head, or leg. Additionally, we found some novel expression patterns for aphid OBPs (Beckendorf et al., 2008). Five OBPs exhibited high-expression levels in the cauda and four in the cornicle (Biasio et al., 2015). Three genes (OBP2/3/15) were highly expressed in the wing (Calvello et al., 2003). Two (OBP3/15) were significantly more highly expressed in the wingless thorax than in the winged thorax with the wings removed, and these transcripts were significantly enriched in the removed wings. More details regarding OBP spatial expression were revealed under our strategy. These findings supported the existence of carrier transport functions other than for foreign chemicals and therefore broader ligand ranges of aphid OBPs. It is important for understanding how insect OBPs function in chemical perception as well as their other potential physiological functions.